Building a Management System to Control the Construction Claims in Iraq - Hadi, Inas Z. (Al-Khwarizmi Engineering Journal, 2018)
The paper deals with claims in construction projects in Iraq and studies their types, causes, impacts, resolution methods and then proposes a management system to control the impacts of claims. Two parts have been done to achieve the research objective (theoretical part and practical part). The findings showed that the main types of the claims are extra work claims, different site condition claims, delay claims and the main causes of the claims are variation of the orders, design errors and omission, delay in payments by owner, variation in quantities and scheduling errors. The claims have bad impacts on the cost by increasing (10% to 25%) and also on the duration of the project by increasing from (25% to 50%).The negotiation is the main method which is used to resolve the claims in the construction project in Iraq. Finally, the proposed claims management system is developed to control the causes of the claims during the preconstruction phase and construction phase.